REGULATORY MECHANISMS IN THE AGRARIAN SECTOR OF UKRAINE: CHALLENGES AND PROSPECTS - Melnychuk Р. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2025)
The agrarian sector is a vital component of Ukraine's economy, playing a crucial role in ensuring the country's food security and contributing to its economic growth. The effective operation of this sector hinges on robust regulatory mechanisms that harmonise the interests of the state, the market, and producers. This article examines contemporary regulatory instruments employed in Ukraine's agrarian sector, identifies challenges encountered during their implementation, and outlines prospects for enhancing the legislative framework and management procedures related to agricultural policy. The research provides a thorough analysis of the current regulatory framework within Ukraine's agrarian sector, focusing on pivotal legislative acts such as the Law of Ukraine "On Agrarian Notes", the Land Code of Ukraine, and the Law of Ukraine "On State Support of Agriculture in Ukraine". Key challenges in the regulatory realm are identified, encompassing issues such as legislative instability, limited access to financial resources, market monopolisation, and the implementation of environmental standards. By employing a comparative approach, the study evaluates international regulatory practices, particularly the experience of the European Union's Common Agricultural Policy and the methods utilised in the United States. It also investigates the effectiveness of financial support mechanisms - such as subsidies, tariffs, and grants - in stimulating agricultural production and adapting to global economic trends. Based on the conducted research, a series of measures are proposed to modernise the legislative framework, optimise institutional management mechanisms, implement innovative technologies within the regulatory process, and enhance the transparency of regulatory procedures. The necessity of aligning national standards with European norms is emphasised, and the concept of clustering is examined as an effective strategy for boosting competitiveness. The findings of this research hold significant practical implications for shaping state agricultural policy, ensuring stable industry development, and facilitating integration into the global economy.